THE ROLE OF AGE ON SPEECH DEVELOPMENT IN SUBJECTS WITH COCHLEAR IMPLANTS - Vesna Lazarovska; Mira Jovanovska (Институт за јавно здравје на Р Северна Македонија = Institute of Public Health of R North Macedonia, 2021)
The cochlear implant has been approved as a method of treating bilateral deep deafness since the 1980s, and since then candidate selection methods have changed several times. Initially, the candidates were only adult patients, and in 1990 the cochlear implant was approved for the first time in children under 2 years of age by the US Food and Drug Administration. In 2000, the same US Administration reduced the limit to one year. The aim of this study was to determine the effect of age at cochlear implantation on speech recognition abilities. Concerning the age groups in which the subjects were assigned to, the best results on the tests were achieved by the group who underwent cochlear implantation at the youngest age. In conclusion, the benefit from cochlear implant in subjects with pre-lingual hearing impairment of the most severe degree has to be stressed and it is much bigger in comparison to individual amplifying hearing aids. If cochlear implant is placed at the youngest age, the results might lead to even 100% of active involvement in the social life of individuals with this kind of impairment.
УЛОГАТА НА ВОЗРАСТА ВРЗ РАЗВОЈОТ НА ГОВОРОТ КАЈ СУБЈЕКТИ СО КОХЛЕАРНИ ИМПЛАНТИ
Keywords: hearing impairment; cochlear implant; rehabilitation treatment; speech development